Intermediate-mass black holes in globular clusters: observations and simulations - Update. Issue Volume 12:Issue S316(2015) (31st March 2017) - Lützgendorf, Nora; Kissler-Patig, Markus; Gebhardt, Karl; Baumgardt, Holger; Kruijssen, Diederik; Noyola, Eva; Neumayer, Nadine; de Zeeuw, Tim; Feldmeier-Krause, Anja; van der Helm, Edwin; Pelupessy, Inti; Zwart, Simon Portegies
Abstract: The study of intermediate-mass black holes (IMBHs) is a young and promising field of research. If IMBH exist, they could explain the rapid growth of supermassive black holes by acting as seeds in the early stage of galaxy formation. Formed by runaway collisions of massive stars in young and dense stellar clusters, intermediate-mass black holes could still be present in the centers of globular clusters, today. We measured the inner kinematic profiles with integral-field spectroscopy for 10 Galactic globular cluster and determined masses or upper limits of central black holes. In combination with literature data we further studied the positions of our results on known black-hole scaling relations (such as M − σ) and found a similar but flatter correlation for IMBHs. Applying cluster evolution codes, the change in the slope could be explained with the stellar mass loss occurring in clusters in a tidal field over its life time. Furthermore, we present results from several numerical simulations on the topic of IMBHs and integral field units (IFUs). N-body simulations were used to simulate IFU data cubes. For the specific case of NGC 6388 we simulated two different IFU techniques and found that velocity dispersion measurements from individual velocities are strongly biased towards lower values due to blends of neighbouring stars and background light. In addition, we use the Astrophysical Multipurpose Software Environment (AMUSE) to combine gravitational physics, stellar evolution and hydrodynamics to simulate the accretion of stellar winds onto a black hole. We find that the S-stars need to provide very strong winds in order to explain the accretion rate in the galactic center.